ANALYSIS OF RELATIONSHIP BETWEEN ENTREPRENEURIAL THINKING AND AGRIBUSINESS MANAGEMENT IN PAGERWOJO DISTRICT, TULUNGAGUNG, EAST JAVA - L. A., Sukma; Suparta, N.; Suarta, G. (Jurnal Peternakan Tropika; Vol 8 No 3 (2020): Vol. 8 No. 3 Tahun 2020; September - December, 2020)
Recently, the term of entrepreneurship is more used, as it is universal in its application, and fits to the context of cultivating entrepreneurship movement and create more Indonesian entrepreneurial thinkers, to develop successful business. The success of agribusiness cannot be determined by farmers alone, but it is a resultant of the synergy between livestock businesses and companies that produce infrastructures and facilities and of companies in processing and marketing their production, as well as their supporting components of agribusiness.  This research aims to study and analyze the relationship between entrepreneurial thinking and agribusiness management of dairy farmers and their successful dairy farmings.  This research was carried out in Pagerwojo District, Tulungagung, East Java with 35 dairy farmers as repondents.  This research used simple random sampling, a simple random method. The results showed that measurement scale used was 1-5 to determine the score of a group of dairy farmers regarding their entrepreneurial thinking; the success of the dairy cattle businesses in Pagerwojo District, Tulungagung, was 5% that was considered as good, shown by the calving interval was 15 ± 2,3 months and flock size was 6 cattle per household or scoring of 3.59%, while the amount of milk production was 3.46%, the number of housing was 4.06% and the growth status was 2, 97%. Keywords : entrepreneurial thinking, dairy farming, agribusiness, success